Anurans of the Agudos and Jaú municipalities, state of São Paulo, Southeastern Brazil - Maffei, Fábio [UNESP]; Nascimento, Bruno Tayar Marinho do [UNESP]; Moya, Guilherme Marson [UNESP]; Donatelli, Reginaldo José [UNESP] (Pensoft Publishers, 2015)
We present a list of amphibian species from the Agudos and Jaú municipalities, a Midwest region of São Paulo state, Brazil. The 26 species recorded exhibited a strong seasonality, with their reproductive periods concentrated in the rainiest months (October and December). Most of the species (88%) are generalists and typically associated with open areas. Although none of the species to be associated exclusively forest environments, the occurrence of some species (12%) depends on the proximity of water bodies for environments with forest formation. Thus, the presence of riparian forest fragments near water bodies is essential for some populations, as these sites are refuge for some species.
Keywords: Amphibians; Atlantic forest; Cerrado; Inventory; Seasonality